Machining Dynamics and Parameters Process Optimization - Urbicain, Gorka; Olvera Trejo, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As we move further into the 21st century, despite the fact that new technologies have emerged, machining remains the key operation to achieve high productivity and precision for high-added value parts in several sectors, but recent advances in computer applications should close the gap between simulations and industrial practices. This book, "Machining Dynamics and Parameters Process Optimization", is oriented toward the different strategies and paths when it comes to increasing productivity and reliability in metal removal processes. The topics include the dynamic characterization of machine tools, experimental dampening techniques, and optimization algorithms combined with signal monitoring.